Clinicopathological Characteristics and Oncological Outcomes of Non-urothelial Bladder Carcinomas: A Multicenter Study - TİNAY, İLKER; KÜTÜKOĞLU, MEHMET UMUT (GALENOS YAYINCILIK, 2021)
Objective: The incidence of non-urothelial bladder cancers is very low, so our knowledge about their treatment protocols and prognosis is limited. We evaluated the clinicopathological characteristics of 26 patients in three different clinics and aimed to determine the prognostic factors affecting oncological outcomes. Materials and Methods: Between January 2012 and October 2019, we retrospectively analyzed the data of twenty-six patients aged between 44-75 years who were diagnosed and treated due to non-urothelial bladder carcinomas in three clinics. Results: Among twenty-six cases, nineteen (73.1%) were male and seven (26.9%) were female. The mean age at diagnosis was 60.77 +/- 8.52. The most common presenting complaint was gross hematuria (84.6%). It was followed by lower urinary tract symptoms (38.4%). Histological types of tumors were squamous cell carcinoma (9 cases, 34.8%), adenocarcinoma (eight cases carrying different histopathologic subtypes: Mucinous, signet ring cell, plasmacytoid/signet ring cell mixed variant and signet ring cell containing osteoclast-like giant cell, 30.8%), small cell carcinoma (3 cases, 11.5%), large cell neuroendocrine carcinoma (2 cases, 7.7%), extra-gastrointestinal stromal tumor (1 case, 3.8%) and malignant undifferentiated mesenchymal tumor (1 case, 3.8%) and leiomyosarcoma (2 cases, 7.6%). At a median follow-up of 13 (2-42) months, the progression-free survival rate was 61.5%, while the overall survival rate was 46.1%. In Kaplan-Meier analysis, the median survival of all cases was found to be 16 (9-33) months. Overall survival times were lower in the presence of advanced (3-4) pathological stages (p=0.006) and higher (>= 2) ECOG scores (p=0.005). Conclusion: In our cases, we observed that overall survival rates increased in patients undergoing multimodal treatments involving radical cystectomy compared to the bladder-sparing approach. The survival rates were higher in squamous cell carcinomas, while the rate of metastasis was higher in adenocarcinoma and neuroendocrine tumors. Up-staging rates after cystectomy were higher in adenocarcinomas, sarcomas and squamous cell carcinomas.
Keywords: Adjuvant chemotherapy; non-urothelial bladder carcinomas; oncological outcomes; radical cystectomy; SQUAMOUS-CELL CARCINOMA; URINARY-BLADDER; RADICAL CYSTECTOMY; PRIMARY ADENOCARCINOMA; NEOPLASMS; SURVIVAL